Kepemimpinan Berbasis Budaya Organisasi dan Kearifan Lokal di Era Globalisasi Pendidikan - Ifqotus Zaroh; Nurhayati Nurhayati; Mohamad Muchlis Solichin; Ali Nurhadi (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Leadership in education plays a strategic role in improving the quality of educational institutions, especially in facing the challenges of globalization and digitalization. Organizational culture and local wisdom are essential elements in shaping students’ character and institutional identity. This study aims to analyze the concept of leadership based on organizational culture and local wisdom, explore the role of local wisdom in educational leadership, and examine its implementation in the era of educational globalization. This research employs a qualitative approach using a library research method. Data were collected through documentation techniques from scientific journals, books, and relevant academic sources published within the last five years. Data analysis was conducted using descriptive qualitative methods through data reduction, data presentation, and conclusion drawing. The findings indicate that leadership based on organizational culture and local wisdom can create a conducive educational environment, strengthen students’ character, and improve the quality of education. In addition, integrating local cultural values with technological innovation is an important strategy for addressing globalization challenges. Therefore, adaptive and contextual leadership rooted in local cultural values is urgently needed in modern educational management.